2018
DOI: 10.1128/aac.02542-17
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Pharmacokinetics and Pharmacodynamics of APX001 against Candida spp. in a Neutropenic Disseminated Candidiasis Mouse Model

Abstract: APX001 is the prodrug of APX001A, which is a first-in-class small molecule with a unique mechanism of action that inhibits the fungal enzyme Gwt1 in the glycosylphosphatidylinositol (GPI) biosynthesis pathway. The goal of the present study was to determine which pharmacokinetic/pharmacodynamic (PK/PD) index and magnitude best correlated with efficacy in the murine disseminated candidiasis model for ( = 5), ( = 5), and ( = 4). MIC values ranged from 0.002 to 0.03 mg/liter for , from 0.008 to 0.06 mg/liter for, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
89
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(95 citation statements)
references
References 26 publications
5
89
0
1
Order By: Relevance
“…A number of compelling study findings were observed. First, the results are consistent with previous findings in an invasive candidiasis murine model demonstrating that AUC/MEC is the most predictive PK/PD index of the microbiological effect (27). Second, the APX001 dose-response relationships were very similar across a diverse set of A. fumigatus strains, as supported by the high R 2 value (0.80) and relatively close fit to the individual stasis and 1-log-kill targets ( Table 2).…”
Section: Figsupporting
confidence: 89%
See 3 more Smart Citations
“…A number of compelling study findings were observed. First, the results are consistent with previous findings in an invasive candidiasis murine model demonstrating that AUC/MEC is the most predictive PK/PD index of the microbiological effect (27). Second, the APX001 dose-response relationships were very similar across a diverse set of A. fumigatus strains, as supported by the high R 2 value (0.80) and relatively close fit to the individual stasis and 1-log-kill targets ( Table 2).…”
Section: Figsupporting
confidence: 89%
“…The median total drug AUC/MEC ratio required to achieve a stasis effect for A. fumigatus was 2,802, and that required to achieve a 1-log kill effect was 5,258. The stasis targets are within the range of AUC/MIC stasis target values that we observed in a murine disseminated candidiasis model with Candida glabrata and Candida auris but notably lower than the values observed with Candida albicans (27). This finding is also reminiscent of that from a PK/PD study with mold-active triazoles, where lower AUC/MEC targets and more fungicidal activity were observed for posaconazole and isavuconazole against A. fumigatus than against C. albicans (35,36,38,39).…”
Section: Figsupporting
confidence: 80%
See 2 more Smart Citations
“…However, a limitation of using cyclophosphamide is that it depletes cells of both the innate and the adaptive immune system (25). At high doses of cyclophosphamide ≥200mg/kg, these deplete Tregs, CD8 + DCs, B-cells and CD4 + and CD8 + T-cells that may be important in immunological studies in response to C. auris (23, 24, 2629).…”
Section: Introductionmentioning
confidence: 99%